当前位置:中文谷 >

习题库

> 若f(x)dx=1,g(x)dx=-3,则[2f(x)+g(x)]dx=(  )A.2            ...

若f(x)dx=1,g(x)dx=-3,则[2f(x)+g(x)]dx=(  )A.2            ...

问题详情:

若f(x)dx=1,g(x)dx=-3,则[2f(x)+g(x)]dx=(  )A.2            ...f(x)dx=1,若f(x)dx=1,g(x)dx=-3,则[2f(x)+g(x)]dx=(  )A.2            ... 第2张g(x)dx=-3,则若f(x)dx=1,g(x)dx=-3,则[2f(x)+g(x)]dx=(  )A.2            ... 第3张[2f(x)+g(x)]dx=(  )

A.2                               B.-3

C.-1                             D.4

【回答】

C [若f(x)dx=1,g(x)dx=-3,则[2f(x)+g(x)]dx=(  )A.2            ... 第4张[2f(x)+g(x)]dx=2若f(x)dx=1,g(x)dx=-3,则[2f(x)+g(x)]dx=(  )A.2            ... 第5张f(x)dx若f(x)dx=1,g(x)dx=-3,则[2f(x)+g(x)]dx=(  )A.2            ... 第6张g(x)dx=2×1-3=-1.]

知识点:导数及其应用

题型:选择题

标签: 2fx fxdx gxdx
  • 文章版权属于文章作者所有,转载请注明 https://zhongwengu.com/exercises/55zqmy.html
推荐文章